(3djS aj cdGe GdYQHs - (3GHf NGdhjg , GdMSjf Hf CMeO Hf NGdhjg Hf MeOGf, CHh YHO Gddg,J (B370 (3g` s ((3jMi GdOjSWi Hf aNQ Hf Ydi Hf TeS GdOjf eMeO GdeGdci s)
(3ChdgG (B:s
(3GdMeO ddg eDLO GdNdb heHOjg , djS ai cdGe GdYQH , EfeG gh Ydi eG CMGW Hg MaXi HGH GdjS ai cdGe GdYQH aYd jaYd eeG djS ajg MQa GdMdb YjfkG HGH djS ai cdGe GdYQH, s
(3BNQgG (B:s
(3hEfeG YjGe ai HjJ hGMO hgh bjGS Ydi YWTGf hYWGT hjfTO hde jaYd ceG aYd GHf bjS hYQa GdUOb ai GdCbhGe fGe Je cJGH (B: (3djS ai cdGe GdYQH eG jLQi eLQGg HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HgG fXGe GdJYbjIs
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B155 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B175s
Keywords: (3GddZIs